2009
DOI: 10.1007/s11325-009-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interval hypoxia on exercise tolerance: special focus on patients with CAD or COPD

Abstract: The mechanisms responsible for these benefits are the increases in total haemoglobin mass, lung diffusion capacity, more efficient ventilation, and a decrease in the responsiveness of the adrenergic system to stimulation and/or an increase in parasympathetic activity. If confirmed in further studies, interval hypoxia might become an attractive strategy to complement the known beneficial effects of exercise training, especially in patients with CAD or COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 75 publications
(128 reference statements)
0
29
0
8
Order By: Relevance
“…Our preliminary data show for the first time that treating athletes with OTS by exposing them to repeated cycles of hypoxia–hyperoxia and light sport‐specific exercise is efficacious to improve their level of performance over a relatively short period of time and to counteract some of the OTS features. After completing the programme, all OTS athletes showed significantly improved tolerance to exercise without significant hematological changes; our findings are consistent with the results of other studies using hypoxia–normoxia exposure as an intervention to improve aerobic capacity in patients (Burtscher et al ., ) and endurance athletes (Katayama et al ., ; Hamlin & Hellemans, ; Burtscher et al ., ). As well, cardiovascular response to a 10‐min continuous HT was also improved and similar to the one recorded in HA.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary data show for the first time that treating athletes with OTS by exposing them to repeated cycles of hypoxia–hyperoxia and light sport‐specific exercise is efficacious to improve their level of performance over a relatively short period of time and to counteract some of the OTS features. After completing the programme, all OTS athletes showed significantly improved tolerance to exercise without significant hematological changes; our findings are consistent with the results of other studies using hypoxia–normoxia exposure as an intervention to improve aerobic capacity in patients (Burtscher et al ., ) and endurance athletes (Katayama et al ., ; Hamlin & Hellemans, ; Burtscher et al ., ). As well, cardiovascular response to a 10‐min continuous HT was also improved and similar to the one recorded in HA.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these strategies have been shown to be effective in improving exercise tolerance and performance in athletes by triggering hematological and nonhematological adaptations, and we found an increased number of reticulocytes after IHHT. Some authors have suggested that intermittent hypoxia can be useful to improve exercise performance in healthy people and CAD patients and other authors have suggested a potential therapeutic role of intermittent hypoxia mainly based on improved hemodynamics and a more efficient respiration . In fact, our results show that IHHT is associated with reduced SBP and DBP and improved left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is a cornerstone in cardiac prevention, and it reduc es total and cardiovascular mortality in patients with CAD . Exposure to normobaric intermittent hypoxia training (IHT) has been shown to improve exercise capacity without exercising in the elderly and in cardiac patients . IHT also positively affects autonomic nervous system functioning in various patients .…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of hypoxic training to improve performance however, varied among different sports [3,4]. The use of hypoxic training has been suggested to be beneficial in conditions such as coronary artery disease and chronic obstructive pulmonary disease [5], despite not commonly used. The purpose of this review was to determine the effectiveness of hypoxic training on cardiometabolic risk factors, which included body weight and body composition, blood glucose, blood pressure, and blood lipid levels.…”
Section: Introductionmentioning
confidence: 99%